The nominal sentence abrogated by letters in the collection of Sarsari (Journal of the College of Basic Education, 2023)
The abrogated nominal sentence (restricted) by letters includes two parts (that and her sisters), and (la) that negates gender, and is likened to (not), and it included her sisters and an indication of each type in it, in addition to citing poetic verses in Al-Sarsari's collection.